(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article presents data where the parameters of the foot in children with scoliosis are studied. The study involved 350 children with scoliosis. Using the method of 3D computer photometry with graphoanalytic interpretation of the image and system analysis, anatomical parameters such as length, width, angle of the 1st and 5th fingers, heel angle were obtained. An automated complex for screening and express diagnostics of flat feet in children with scoliosis has been developed.